Mechanisms of self-screening in intrinsic semiconductors - Chikina, I.; Shikin, V. (Recent Contributions to Physics, 2015)
Electron-hole pairs (proton-hydroxyl pairs in water) thermally activated in intrinsic semiconductors interact through Coulomb forces which necessarily results in some self-screening that should either be accounted for in a proper way or shown to be negligible. Possible mechanisms of self-screening are considered in this work.